Identification of two novel thiazolidin-2-imines as tyrosinase inhibitors: synthesis, crystal structure, molecular docking and DFT studies. Issue 8 (August 2022) - Shehzadi, Syeda Aaliya; Saeed, Aamer; Perveen, Fouzia; Channar, Pervaiz Ali; Arshad, Ifzan; Abbas, Qamar; Kalsoom, Saima; Yousaf, Sammer; Simpson, Jim
Abstract: Various N - and S -containing 5-membered heterocycles such as imidazole-2-thiones, thiazolidinones and thiazolidin-2-imines are among the most eminent biologically active organic heterocycles and are present in many marketed drugs. In view of their synthetic and biological significance, an efficient synthesis of two novel thiazolidine-2-imines (4a-b ) utilizing a three-component one-pot approach starting from an aldimine, an alkyne and isothiocyanates has been developed. The reaction proceeded via a 5-exo digonal ( 5-exo dig) cyclization of a propargyl thiourea, formed in situ in the presence of Zn (II) -catalyst. The structures of the resulting products are elucidated by spectroscopic methods and X-ray crystallography. A DFT study explored the structural, thermodynamic and molecular electrostatic potential parameters for the compounds. The newly synthesized compounds (4a & 4b ) were evaluated for the inhibition of tyrosinase both in vitro and in silico . The in vitro results revealed that the synthesized thiazolidine-2-imines (4a-b ) showed good inhibition activity towards mushroom tyrosinase (IC50 = 1.151 ± 1.25 and 2.079 ± 0.87 μM respectively) in comparison to the kojic acid standard (IC50 = 16.031 ± 1.27 μM) a commonly used anti-pigment agent in plant and animal tissues. The experimental inhibition was further assessed by molecular docking studies between synthesized ligands and the human tyrosinase protein complex to investigate the intermolecular interactions responsible for tyrosinase inhibition activity. Graphical abstract: Image 1 Abstract : N, S -heterocycles; Thiazolidine-2-imines; Crystal structures; DFT studies; Molecular docking; Tyrosinase inhibitors.